2020
DOI: 10.3892/ijmm.2020.4781
|View full text |Cite
|
Sign up to set email alerts
|

BCL2‑regulated apoptotic process in myocardial ischemia‑reperfusion injury (Review)

Abstract: The leading cause of death in developed countries is cardiovascular disease, where coronary heart disease is the main cause of death. Myocardial reperfusion is the most significant method to prevent cell death after ischemia. However, restoration of blood flow may paradoxically lead to myocardial ischemia-reperfusion injury (MI/RI) accompanied by metabolic disturbances and cardiomyocyte death. As the myocardium has an extremely limited ability to regenerate, the mechanisms of regulated cell death, including ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 169 publications
(267 reference statements)
1
26
1
3
Order By: Relevance
“…In addition, in some studies on other apoptotic factors and TBI, there was a significant enhancement in CSF apoptotic factors (14,15). Korshunova et al observed that Bcl-2 could regulate apoptotic factors in myocardial ischemia/reperfusion injury (16). However, these studies were different from our study in terms of protocols.…”
Section: Discussioncontrasting
confidence: 85%
“…In addition, in some studies on other apoptotic factors and TBI, there was a significant enhancement in CSF apoptotic factors (14,15). Korshunova et al observed that Bcl-2 could regulate apoptotic factors in myocardial ischemia/reperfusion injury (16). However, these studies were different from our study in terms of protocols.…”
Section: Discussioncontrasting
confidence: 85%
“…The Bcl-2 family is involved in the intrinsic pathway of apoptosis; it includes proapoptotic proteins (such as Bad, Bax or Bid) and antiapoptotic proteins (such as Bcl-2 and Bcl-XL). Bcl-2 is regulated by several signaling pathways and substances, including JAK2/STAT3, PI3K/AKT, MEK1/ERK1/2, PTEN, cardiac ankyrin repeat protein, eNOS, and miRs [ 45 ]. Bcl2 is the target gene of miR-503 [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that apoptosis plays an important role in cardiomyocyte death and is proposed to contribute to nal infarct size [28,29]. A pivotal event in the initiation of apoptotic cell death is ERS [6].…”
Section: Discussionmentioning
confidence: 99%